Ethnopharmacological activity of Hedera nepalensis K. Koch extracts and lupeol against alloxan-induced type I diabetes - Waleed Javed Hashmi; Hammad Ismail; Laila Jafri; Bushra Mirza (Universidade de São Paulo, 2020)
In this study, we investigated the protective effects of Hedera nepalensis crude extract, its fractions and lupeol in alloxan-induced diabetic rats. Lupeol and n-hexane (HNN) fraction significantly reduced the blood glucose level by increasing insulin level in time dependent manner, and also significantly increased amylase and lipase activity in diabetic rats. Elevated levels of alanine transaminases (ALT), aspartate transaminases (AST), thiobarbituric acid reactive substances (TBARS), nitrite, hydrogen peroxide (H2O2), total bilirubin and total protein in blood serum were efficiently restored to normal levels. Suppressed enzymatic activity of catalase (CAT), superoxide dismutase (SOD), reduced glutathione (GSH) and peroxidase (POD) were also restored to their normal levels. Kidney functions were also restored to normal level after treatment with HNN and lupeol. HNN fraction and lupeol of H. nepalensis prevented oxidative stress in alloxan-induced diabetic rats. This study signifies the importance of H. nepalensis and lupeol in ameliorating diabetes by inducing insulin secretion in diabetic model rats.